Longitudinal Analysis of the Relationship Between Perceived Norms and Sharing Injection Paraphernalia - Davey-Rothwell, Melissa A. (2009)
Despite decline in needle sharing in some countries, many injectors continue to share injection paraphernalia such as cookers and cotton. While individual and structural factors are associated with injection risk behavior, little attention has been given to the influence of social network members, such as norms, on injection paraphernalia sharing. The present study is a longitudinal analysis of the association between perceived norms and sharing syringes and non-syringe injection paraphernalia. Participants were enrolled in the STEP into Action study and reported injection drug use at both baseline and follow-up assessments (n = 398). Results showed that descriptive norms, or believing that peers practiced risky injection behaviors, predicted sharing both syringes and nonsyringe paraphernalia. However, there was no association between injunctive norms (i.e., perceived peer approval) and either syringe or non-syringe paraphernalia sharing. Changing norms may lead to sustained behavior change. Accessible, norms-based interventions are needed to discourage drug injectors from sharing injection paraphernalia.